Anti-clastogenic effect of beta-glucan extracted from barley towards chemically induced DNA damage in rodent cells - Angeli, J. P. F.; Ribeiro, L. R.; Bellini, M. F.; Mantovani, M. S. (Hodder Arnold, Hodder Headline Plc, 2006)
beta-Glucan (BG) was tested in vitro to determine its potential clastogenic and/or anti-clastogenic activity, and attempts were made to elucidate its possible mechanism of action by using combinations with an inhibitor of DNA polymerase. The study was carried out on cells deficient (CHO-k1) and cells proficient (HTC) in phases I and II enzymes, and the DNA damage was assessed by the chromosomal aberration assay. BG did not show a clastogenic effect, but was anti-clastogenic in both cell lines used, and at all concentrations tested (2.5, 5 and 10 mg/mL) in combination with damage inducing agents (methylmethane sulfonate in cell line CHO-k1, and methylmethane sulfonate or 2-aminoanthracene in cell line HTC). BG also showed a protective effect in the presence of a DNA polymerase beta inhibitor (cytosine arabinoside-3-phosphate, Ara-C), demonstrating that BG does not act through an anti-mutagenic mechanism of action involving DNA polymerase beta.
Keywords: anti-mutagenesis; beta-glucans; chromosomal aberrations; drug-metabolizing cells